Liquid-Phase Synthesis of Cyanuric Acid from Urea - She, Dong-Mei; Yu, Hai-Lin; Huang, Qi-Liang; Li, Fen-Ming; Li, Chun-Jiu (Molecules (Basel, Switzerland), 2010)
The focus of this paper was to identify a cheaper solvent from among diesel fuel, kerosene, sulfolane or a mixture of sulfolane and cyclohexanol for the preparation of cyanuric acid heterocyclization of urea. To obtain a higher yield, the effects of catalyst (sodium, ammonium, calcium and zinc salts) and temperature (160 °C to 220 °C) on the trimerization of urea were also carefully studied. We established the optimal reaction conditions and further validated them in our scale-up experiments.